Answer:
p = -6
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define equation
4 - 3p = 22
Step 2: Solve for p
- Subtract 4 on both sides: -3p = 18
- Divide -3 on both sides: p = -6
Step 3: Check
Plug in p into the original equation to verify it's a solution.
- Substitute in p: 4 - 3(-6) = 22
- Multiply: 4 + 18 = 22
- Add: 22 = 22
Here we see that 22 does indeed equal 22.
∴ p = -6 is a solution to the equation.